The cellular localization of avian influenza virus PB1-F2 protein alters the magnitude of IFN2 promoter and NFκB-dependent promoter antagonism in chicken cells. (23rd January 2019) - James, Joe; Smith, Nikki; Ross, Craig; Iqbal, Munir; Goodbourn, Steve; Digard, Paul; Barclay, Wendy S.; Shelton, Holly
Abstract : The accessory protein, PB1-F2, of influenza A virus (IAV) functions in a chicken host to prolong infectious virus shedding and thus the transmission window. Here we show that this delay in virus clearance by PB1-F2 in chickens is accompanied by reduced transcript levels of type 1 interferon (IFN)-induced genes and NFκB-activated pro-inflammation cytokines. In vitro, two avian influenza isolate-derived PB1-F2 proteins, H9N2 UDL01 and H5N1 5092, exhibited the same antagonism of the IFN and pro-inflammation induction pathways seen in vivo, but to different extents. The two PB1-F2 proteins had different cellular localization in chicken cells, with H5N1 5092 being predominantly mitochondrial-associated and H9N2 UDL being cytoplasmic but not mitochondrial-localized. We hypothesized that PB1-F2 localization might influence the functionality of the protein during infection and that the protein sequence could alter cellular localization. We demonstrated that the sequence of the C-terminus of PB1-F2 determined cytoplasmic localization in chicken cells and this was linked with protein instability. Mitochondrial localization of PB1-F2 resulted in reduced antagonism of an NFκB-dependent promoter. In parallel, mitochondrial localization of PB1-F2 increased the potency of chicken IFN 2 induction antagonism. We suggest that mitochondrial localization of PB1-F2 restricts interaction with cytoplasmic-located IKKβ, reducing NFκB-responsive promoter antagonism, but enhances antagonism of the IFN2 promoter through interaction with the mitochondrial adaptor MAVS. Our study highlights the differential mechanisms by which IAV PB1-F2 protein can dampen the avian host innate signalling response.